Assessment of Adenosine Triphosphatase Phospholipid Transporting 8B1 (ATP8B1) Function in Patients With Cholestasis With ATP8B1 Deficiency by Using Peripheral Blood Monocyte‐Derived Macrophages. Issue 1 (26th September 2020) - Mizutani, Ayumu; Sabu, Yusuke; Naoi, Sotaro; Ito, Shogo; Nakano, Satoshi; Minowa, Kei; Mizuochi, Tatsuki; Ito, Koichi; Abukawa, Daiki; Kaji, Shunsaku; Sasaki, Mika; Muroya, Koji; et al.
Abstract : Adenosine triphosphatase phospholipid transporting 8B1 (ATP8B1) deficiency, an ultrarare autosomal recessive liver disease, includes severe and mild clinical forms, referred to as progressive familial intrahepatic cholestasis type 1 (PFIC1) and benign recurrent intrahepatic cholestasis type 1 (BRIC1), respectively. There is currently no practical method for determining PFIC1 or BRIC1 at an early disease course phase. Herein, we assessed the feasibility of developing a diagnostic method for PFIC1 and BRIC1. A nationwide Japanese survey conducted since 2015 identified 25 patients with cholestasis with ATP8B1 mutations, 15 of whom agreed to participate in the study. Patients were divided for analysis into PFIC1 (n = 10) or BRIC1 (n = 5) based on their disease course. An in vitro mutagenesis assay to evaluate pathogenicity of ATP8B1 mutations suggested that residual ATP8B1 function in the patients could be used to identify clinical course. To assess their ATP8B1 function more simply, human peripheral blood monocyte‐derived macrophages (HMDMs) were prepared from each patient and elicited into a subset of alternatively activated macrophages (M2c) by interleukin‐10 (IL‐10). This was based on our previous finding that ATP8B1 contributes to polarization of HMDMs into M2c. Flow cytometric analysis showed that expression of M2c‐related surface markers cluster of differentiation (CD)14 and CD163 were 2.3‐fold and 2.1‐fold lower (95% confidence interval, 2.0‐2.5 for CD14 and 1.7‐2.4 for CD163), respectively, in patients with IL‐10‐treated HMDMs from PFIC1 compared with BRIC1. Conclusion : CD14 and CD163 expression levels in IL‐10‐treated HMDMs may facilitate diagnosis of PFIC1 or BRIC1 in patients with ATP8B1 deficiency.